1993
DOI: 10.1093/infdis/167.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Transmission of Human T Cell Leukemia/Lymphoma Virus Type I among Married Couples in Southwestern Japan: An Initial Report from the Miyazaki Cohort Study

Abstract: To identify factors that may modify the heterosexual transmission of human T cell leukemia/lymphoma virus type I (HTLV-I), 534 married couples enrolled in the Miyazaki Cohort Study between November 1984 and April 1989 were studied: 95 husband HTLV-I-seropositive (H+)/wife seropositive (W+), 33 H+/W-, 64 H-/W+, and 342 H-/W-. After 5 years of follow-up, seven seroconversions occurred and clustered significantly among serodiscordant pairs (relative risk [RR] = 41.2); the rate of transmission was 3.9 times higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
4
10

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 34 publications
3
103
4
10
Order By: Relevance
“…The results of this study are in contrast to the fi nding of 2.5 transmissions/100py by Stuver et al 66 in a Miyazaki cohort of southeastern Japanese couples; however, Roucoux et al included a higher number of couples with HTLV-1 infections that were, on average, much older and in longer relationships (>360 vs. 72 months). Larsen et al 67 reported an overall HTLV prevalence of 3.6% (76 of 2,127 subjects) in an adult population living in urban areas in Guinea-Bissau, Africa, and the prevalence rates among men and women were 2.2% and 4.7%, respectively.…”
Section: Sexual Transmissioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this study are in contrast to the fi nding of 2.5 transmissions/100py by Stuver et al 66 in a Miyazaki cohort of southeastern Japanese couples; however, Roucoux et al included a higher number of couples with HTLV-1 infections that were, on average, much older and in longer relationships (>360 vs. 72 months). Larsen et al 67 reported an overall HTLV prevalence of 3.6% (76 of 2,127 subjects) in an adult population living in urban areas in Guinea-Bissau, Africa, and the prevalence rates among men and women were 2.2% and 4.7%, respectively.…”
Section: Sexual Transmissioncontrasting
confidence: 99%
“…In addition, the epidemiology of HTLV, particularly its tendency to occur in clusters, has enabled the identifi cation of groups who are at risk for exposure, including injection drug users 34,56,59 , sex workers 50,[55][56][57][58][59][60][61][62] , men who engage in intercourse with other men 52,53,56 , recipients of blood transfusions in Brazil before November 1993 63 , and sexual partners of known HTLV carriers [64][65][66] (Figure 2). …”
Section: Sexual Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…A diferencia de otros integrantes de la familia viral, como el HIV, el HTLV-I es menos infeccioso y su transmisión suele requerir el contacto directo entre células 9 . La transmisión vía sexual ocurre de manera inadvertida para el paciente y existe una mayor prevalencia en mujeres, debido al mayor éxito de transmisión del hombre hacia la mujer, dada su fuerte asociación con las células que lo transmiten 10 . Es así como las experiencias clínicas demuestran que la transmisión del virus en matrimonios, requiere de una exposición prolongada por varios años para que ésta ocurra 10,11 .…”
unclassified